GagCM9-specific CD8+ T cells expressing limited public TCR clonotypes do not suppress SIV replication in vivo. - Lara Vojnov; Mauricio A Martins; Jorge R Almeida; Zachary Ende; Eva G Rakasz; Matthew R Reynolds; Enrique J Leon; Kim L Weisgrau; Benjamin J Burwitz; Joy M Folkvord; Marlon G Veloso de Santana; Patrícia C Costa Neves; et al. (PLoS ONE)
Several lines of evidence suggest that HIV/SIV-specific CD8(+) T cells play a critical role in the control of viral replication. Recently we observed high levels of viremia in Indian rhesus macaques vaccinated with a segment of SIVmac239 Gag (Gag(45-269)) that were subsequently infected with SIVsmE660. These seven Mamu-A*01(+) animals developed CD8(+) T cell responses against an immunodominant epitope in Gag, GagCM9, yet failed to control virus replication. We carried out a series of immunological and virological assays to understand why these Gag-specific CD8(+) T cells could not control virus replication in vivo. GagCM9-specific CD8(+) T cells from all of the animals were multifunctional and were found in the colonic mucosa. Additionally, GagCM9-specific CD8(+) T cells accessed B cell follicles, the primary residence of SIV-infected cells in lymph nodes, with effector to target ratios between 20-250 GagCM9-specific CD8(+) T cells per SIV-producing cell. Interestingly, vaccinated animals had few public TCR clonotypes within the GagCM9-specific CD8(+) T cell population pre- and post-infection. The number of public TCR clonotypes expressed by GagCM9-specific CD8(+) T cells post-infection significantly inversely correlated with chronic phase viral load. It is possible that these seven animals failed to control viral replication because of the narrow TCR repertoire expressed by the GagCM9-specific CD8(+) T cell population elicited by vaccination and infection.